Kenya Economic Update, June 2012 : Walking on a Tightrope--Rebalancing Kenya's Economy with a Special Focus on Regional Integration - World Bank (World Bank, Nairobi, 2017)
In 2012, Kenya's economy has been on a tightrope. Policy makers have had to walk a fine line between stabilizing the economy and maintaining the growth momentum. While inflation has declined, the exchange rate stabilized, and the fiscal position improved, fundamental economic imbalances continue to make Kenya vulnerable to shocks. In the absence of economic and social turbulence, Kenya should grow at 5 percent in 2012 and 2013, which will still be substantially below its neighbors. Kenya has been benefitting from the integration and growth momentum in the East African Community (EAC), which has become one of the most vibrant economic regions in the world. However, despite impressive increases in trade between the five EAC partners in recent years, there is still a large untapped potential. EAC trade can increase several-fold if unnecessary restrictions in the trade of goods and services particularly nontariff barriers were removed.